Innovative Materials And Techniques For Osteochondral Repair. - Benea, Horea (Materials research foundations ;, 2019)
The book presents research in treating focal joint cartilage defects. Keywords: Biomaterials, Osteochondral Repair, Lipoaspirate Fluid (LAF) Cells, Arthrosis, Focal Joint Cartilage Defects, Physiopathology of Cartilage Lesions, Diagnosis of Cartilage Lesions, Treatment of Cartilage Lesions, Plastic Surgery, Vascular Surgery, Repair Surgery, Orthopedics, Biological Arthroplasties.